Fuzzy querying with the use of interval-valued fuzzy sets - Myszkorowski, Krzysztof; Superson, Izabela (Wydawnictwo Politechniki Łódzkiej, 2013)
The paper deals with flexible queries in relational databases. Conditions included in queries are modeled with the use of interval-valued fuzzy sets. Each value returned by a query is associated with a subinterval of [0,1] which expresses a membership degree. The bounds of membership intervals have been determined for different operations of relational algebra and different SQL operators.